Classroom Management to Increase Student Activeness in Elementary School Social Studies Courses - Ferdiyansyah, Aldy (JEID: Journal of Educational Integration and Development, 2024)
The suboptimal classroom management has an impact on student activity in lectures. This study uses a pre-experimental design method with a quantitative approach. The results of the paired sample test calculation showed a significance value of 0.000 which is less than 0.05. So it can be interpreted that there is a significant difference between the results of the pretest and posttest, in other words, classroom management has an effect on increasing student activity in elementary school social studies courses. The level of effectiveness of the use of the role playing model is included in the moderate category based on the results of the N-Gain test with an average gain score of 0.5. Based on the results of the study, it is expected that other relevant studies with a wider scope will be carried out in order to produce more perfect and useful findings.